2015
DOI: 10.1016/j.jretconser.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Engaging consumers on new integrated multichannel retail settings: Challenges for retailers

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 226 publications
(171 citation statements)
references
References 55 publications
5
151
1
14
Order By: Relevance
“…According to consumers' comments who participated in this research, the availability of the products and the features of the location that they can purchase the product maintain important impacts on the rate of new product purchase. This is consistent with previous studies (Pantano & Viassone, 2015). Previous studies revealed that the brand reputation, previous experience, health slogans and others recommendations have positive effects on customer choice (Di Monaco et al, 2004;Gielens, 2007;Khodayari, 2013), although the impact of advertising is different according to different countries (Gielens, 2017;Mahdavi Mazdeh et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to consumers' comments who participated in this research, the availability of the products and the features of the location that they can purchase the product maintain important impacts on the rate of new product purchase. This is consistent with previous studies (Pantano & Viassone, 2015). Previous studies revealed that the brand reputation, previous experience, health slogans and others recommendations have positive effects on customer choice (Di Monaco et al, 2004;Gielens, 2007;Khodayari, 2013), although the impact of advertising is different according to different countries (Gielens, 2017;Mahdavi Mazdeh et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Past studies have indicated that the space and decoration of the store can affect customer's behavior (Pantano & Viassone, 2015). Also a great number of customers want high performance and do not like surprising stores.…”
Section: Placementioning
confidence: 99%
“…Mobile devices can bridge that gap by bringing the online experience into the brick-and-mortar store. In addition, the combination of interactive and entertaining technologies attracts more consumers and improves the shopping experience (Demirkan & Spohrer, 2014;Pantano & Viassone, 2015;Papagiannidis, Pantano, See-To, & Bourlakis, 2013;Poncin & Ben Mimoun, 2014). The growing role of in-store technologies also creates an additional dimension.…”
Section: Monográficomentioning
confidence: 99%
“…Retailers need to develop ad-hoc capabilities for integrating their own knowledge and skills with the ones emerging by interactions with consumers in the development of new customised services (Chathoth et al, 2013;Gustafsson et al, 2012;Lusch et al, 2006). These new services better satisfy consumers' needs due to the level of customisation provided by the clients' involvement in the service co-creation (Ngo and O'Cass, 2013;Pantano and Viassone, 2015;Zwass, 2010). From a managerial point of view, this scenario for future retailing foresees a large usage of self-service technologies that facilitate reducing operating costs, service delivery, and consumer customisation.…”
Section: Introductionmentioning
confidence: 99%